Effect of potassium on growth, yield and quality of pineapple in tropical peat - Razzaque, A.H.M.; Hanafi, Mohamed Musa (Cirad/EDP Sciences, 2001)
Two field experiments were conducted to investigate the effects of potassium (K) on plant growth, fruit yield and quality of pineapple cultivated on tropical peat soil. Materials and methods. Six levels of K: 0, 266, 532, 798, 1064 and 1330 kg.ha-1 K2O were applied at each of two pineapple plantations located at two different sites. The experiments were conducted with the Gandul cv. in a randomized complete block design with three replications. Results and discussion. The application of K had not any significant effect on plant height and leaf number of pineapple at both sites. Potassium significantly influenced the fruit diameter at site 1, and fruit length and fruit weight at site 2. The application of 266 kg.ha-1 K2O resulted in the highest fruit weight and, at site 2, further increase of K declined it. Potassium had no significant effect on fruit sugar and acidity. However, at site 2, acid content tended to increase with increased K applications. Conclusion. Potassium applications at high rates tended to depress most of the growth and yield attributes of cv. Gandul pineapple cultivated on peat soil in Malaysia.